Sustainable Production of Bioethanol Using Levulinic Acid Pretreated Sawdust - Nawaz, Ali; Huang, Rong; Junaid, Farah; Feng, Yiwei; Haq, Ikram Ul; Mukhtar, Hamid; Jiang, Kankan (Frontiers in Bioengineering and Biotechnology, 2022)
The sustainability and the economic viability of the bioethanol production process from lignocellulosic biomass depend on the efficient and effective pretreatment of biomass. The traditional pretreatment strategies implicating the use of mineral acids, alkalis, and organic solvents release toxic effluents and the formation of inhibitory compounds posing detrimental effects on the environment and interfering with the process of enzymatic saccharification respectively. Ionic liquids (ILs) as green solvents were used to overcome this issue but Deep eutectic Solvent as an emerging class of ionic liquids performed better in terms of making the process environmentally and economically viable. The green solvent-based pretreatment strategy applied in the current research was levulinic acid-based Natural Deep Eutectic Solvent (NADES). Three different Hydrogen Bond Acceptors (HBAs), acetamide, betaine, and choline chloride in combination with levulinic acid as Hydrogen Bond Donor (HBD) in (HBD: HBA) molar ratio 2:1 were screened for biomass pretreatment. The best DES was levulinic acid: choline chloride in an optimized molar ratio of 1:0.5 resulting in 91% delignification. The physicochemical parametric optimization of saccharification, exhibited maximum enzymatic hydrolysis of 25.87% with 125 mg of pretreated sawdust via simultaneous addition of three thermostable cellulases i.e., Endo-1,4-β-D-glucanase (240 U), Exo-1,4-β-D-glucanase (180 U) and β-glucosidase (320 U) for 5 hours of incubation at 75℃. The reducing sugar slurry obtained from the saccharified biomass was then added to a fermentation medium for bioethanol production and a maximum of 11.82% of production was obtained at 30℃, 72 hours, and 180 rpm using a 2.5% 24 hours old Saccharomyces cerevisiae seed culture. The current study revealed that levulinic-based deep eutectic solvent exhibited remarkable delignification which led to the efficient enzymatic hydrolysis of sawdust and hence bioethanol production. Furthermore, it will prospect new avenues in bioethanol production using a deep eutectic solvent. Deep eutectic solvent overcame the issues posed by ionic liquids i.e. toxicity, expensive and complex preparation as well as non-biodegradability.